2021
DOI: 10.1080/15384047.2020.1861923
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic enhancement of radiation and immunomodulation by gold nanoparticles in triple negative breast cancer

Abstract: Gold nanoparticles (AuNPs) have been shown to enhance cancer radiotherapy (RT) gain by localizing the absorption of radiation energy in the tumor while sparing surrounding normal tissue from radiation toxicity. Previously, we showed that AuNPs enhanced RT induced DNA damage and cytotoxicity in MCF7 breast cancer cells. Interestingly, we found that cancer cells exhibited a size-dependent AuNPs intracellular localization (4 nm preferentially in the cytoplasm and 14 nm in the nucleus). We extended those studies t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 83 publications
0
21
0
Order By: Relevance
“… 25 , 26 Radiotherapy is also a treatment that can induce ICD in tumour cells, and the presence of radiotherapy sensitizer AuNPs may enhance this effect. 46 However, the combination of the two can induce stronger ICD effects in tumour cells and induce the activation and maturation of BMDCs. Tumour vaccine experiment results have shown that the injection of dying necroptotic cancer cells directly leads to more effective control of tumour growth in mice.…”
Section: Discussionmentioning
confidence: 99%
“… 25 , 26 Radiotherapy is also a treatment that can induce ICD in tumour cells, and the presence of radiotherapy sensitizer AuNPs may enhance this effect. 46 However, the combination of the two can induce stronger ICD effects in tumour cells and induce the activation and maturation of BMDCs. Tumour vaccine experiment results have shown that the injection of dying necroptotic cancer cells directly leads to more effective control of tumour growth in mice.…”
Section: Discussionmentioning
confidence: 99%
“…RT exerts cytotoxic and cytostatic effects via DNA damage by fractionated focal irradiation ( 81 ). However, these irradiations are unable to differentiate tumor cells from normal cells which lead to unnecessary destruction of surrounding healthy tissues ( 82 ). Additionally, its tumoricidal ability is often limited by the maximum deposited dosage and that has always remained a challenge among radiologists ( 83 ).…”
Section: Radiation Therapy With Gold Nanoparticlesmentioning
confidence: 99%
“…Generation of reactive oxygen species (ROS) can be induced by the Auger electron production from the surface of AuNPs ( 20 ). By coupling with an active targeting strategy or by the passive targeting of the EPR effect alone, using AuNPs as radiosensitizers allows the reduction of total RT dosage whilst increasing the local RT dosage to tumor sites ( 82 ). For example, conjugation of Tz to PEG-AuNPs (Tz-PEG-AuNPs) allowed intracellular uptake of AuNPs into SK-BR-3 human breast cancer cells, which then proceeded to cause DNA double-strand breaks by 3.3 to 5.1 times more than RT alone or RT with PEG-AuNPs ( 88 ).…”
Section: Radiation Therapy With Gold Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Auaided radiotherapy (RT) is useful for making tumors more sensitive to radiation damage because of an enhancement of the radiation dose in the tumor region. This enhancement occurs primarily due to the photoelectric cross section which is much higher for Au (Z = 79) as compared to tumor tissue (Bromma et al 2020;Cho 2005;Choi et al 2020;Janic et al 2021;Chow 2020a, 2020b). Hainfeld and coworkers (Hainfeld et al 2010) demonstrated that Au NPs are non-toxic up to a mass concentration of 20 mg/g when studying a murine squamous cell carcinoma cell line (SCC VII).…”
Section: Introductionmentioning
confidence: 99%